2019
DOI: 10.1371/journal.pone.0216417
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-dependent, swimming-induced paralysis arises as a consequence of loss of function mutations in the RUNX transcription factor RNT-1

Abstract: Dopamine (DA) is a neurotransmitter with actions across phylogeny that modulate core behaviors such as motor activity, reward, attention, and cognition. Perturbed DA signaling in humans is associated with multiple disorders, including addiction, ADHD, schizophrenia, and Parkinson’s disease. The presynaptic DA transporter exerts powerful control on DA signaling by efficient clearance of the neurotransmitter following release. As in vertebrates, Caenorhabditis elegans DAT (DAT-1) constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Hardaway et al, 2015;J. A. Hardaway et al, 2012;Robinson et al, 2019;Safratowich et al, 2013). The free-living C. elegans hermaphrodite possesses 8 mechanosensitive DA neurons that inhibit motor neurons involved in determining the speed of crawling on solid surfaces or thrashing in liquid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hardaway et al, 2015;J. A. Hardaway et al, 2012;Robinson et al, 2019;Safratowich et al, 2013). The free-living C. elegans hermaphrodite possesses 8 mechanosensitive DA neurons that inhibit motor neurons involved in determining the speed of crawling on solid surfaces or thrashing in liquid.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have made use of the nematode model to study DAT-dependent DA signaling (Bermingham et al, 2017;Carvelli et al, 2010;J. A. Hardaway et al, 2012;Nass et al, 2002;Robinson et al, 2019).…”
Section: Significance Statementmentioning
confidence: 99%
“…Apart from the DA neuron cell‐autonomous role for rnt‐1 in producing Swip, the gene appears to have roles in other cell types. In fact, rnt‐1 (vt34) exhibits altered synaptic transmission capacity as demonstrated by aldicarb and levamisole assays, suggesting a disrupted ACh signaling at neuromuscular junctions (Robinson et al, 2019). Although Runx transcription factors have well‐established roles in neural development, postmitotic neural functioning, and support of damaged neural tissue in mammals (Wang & Stifani, 2017), these findings are the first to demonstrate a role for proteins of this class in the regulation of DA signaling.…”
Section: Swip Screening Identifies Novel Molecular Contributors To Da...mentioning
confidence: 99%
“…Line vt34(Robinson et al, 2019) was found to encode a mutant allele of the C. elegans gene encoding the Runt-related (Runx) transcription factor, rnt-1, which functions as a dimer with the protein encoded by bro-1, whose mutation also was found to cause Swip. Reduced levels of dat-1 and cat-2 expression were observed in rnt-1 mutants, indicative of the role of rnt-1 in defining limits to DA signaling.…”
mentioning
confidence: 99%
“…Deletion of dat‐1 causes accumulation of extracellular dopamine into the synaptic cleft resulting in a swimming‐induced paralysis (SWIP) behavioral phenotype (Hardaway et al., 2012; McDonald et al., 2007). Dynamic regulation of the dat‐1 gene influences DAT‐1 expression and is likely to modulate behavioral effects observed by its deletion (Felton & Johnson, 2014; Robinson et al., 2019).…”
Section: Introductionmentioning
confidence: 99%